Prototyping Interface for a Website-Based Visitor Management System of Gili Tramena: A Design Thinking Approach: Prototipe Antarmuka Visitor Management System Gili Tramena Berbasis Website: Sebuah Pendekatan Design Thinking - Amara, Nadya; Noor Alamsyah; Ramaditia Dwiyansaputra (Journal of Computer Science and Informatics Engineering (J-Cosine), 2025)
Gili Tramena which stands for Gili Trawangan, Gili Air and Gili Meno. The three Gili Islands are one of the tourist destinations that are visited by many tourists, both local and foreign tourists because of their underwater power. The high flow of tourists has both positive and negative impacts from an economic, social and environmental perspective. The positive impacts of increased tourism include economic improvement in Gili Tramena, globalization of Indonesian tourism, and improvement of public infrastructure. The negative impacts of increased tourism include cultural change, economic dependency, degraded water quality, and damage to coral reefs. These negative impacts will continue if the number of tourists continues to increase. One way to prevent this is to limit the number of visitors to Gili Tramena each day. Tourist data collection, which is still done manually, is also the reason for the difficulty in controlling tourists entering Gili Tramena. One way to streamline visitor data collection is through a Visitor Management System (VMS). This VMS will help to collect data systematically. Therefore, it is necessary to design a UI/UX VMS information system to limit and control visitors entering Gili Tramena. The UI/UX design of the Tramena VMS was carried out using the Design Thinking approach with 5 stages, namely Emphatize, Define, Ideate, Prototype, and Test. Based on the results of testing using the SUS (System Usability Score) method, a score of 85.92 was obtained, which indicates that this system is included in the "Excellent" category, with the UI/UX design meeting high standards in terms of usability, efficiency, and overall user experience. It is expected that this system can be further developed with the actual implementation of the designed design.